Perceived ease of use and trust towards intention to use online banking in Malaysia / Siti Rapidah Omar Ali - Omar Ali, Siti Rapidah; Wan Marzuki, Wan Nur Khadijah; Mohd Said, Nur Shafini; Abdul Manaf, Suhaily Maizan; Adenan, Nur Dalila (Universiti Teknologi MARA, Perlis, 2020)
The development and invention of technology has transformed the way organizations conduct their businesses currently including banking institutions mainly in offering online banking services. Since the year of 2000, online banking services have been introduced in Malaysia. Still, online banking users in Malaysia are intolerant by issues of trust towards online banking which affect their level of acceptance. This study aims to identify the effect of perceived ease of use and trust towards intention to use internet banking among staff in Municipal Council in Malaysia. Technology Acceptance Model (TAM) was used as a research framework. 265 online banking users in a Municipal Council in Malaysia were tested using self-administered questionnaire. To examine the relationship between perceived ease of use and trust towards the intention to use internet banking, Pearson correlation and multiple regression were employed. The findings showed that perceived ease of use and trust have significant relationship with the intention to use internet banking. The outcomes offered valued information for both financiers and policy makers particularly when designing online banking marketing approaches.